ATIM-28. PHASE II TRIAL OF AV-GBM-1 (AUTOLOGOUS DENDRITIC CELLS LOADED WITH TUMOR ASSOCIATED ANTIGENS) AS ADJUNCTIVE THERAPY FOLLOWING SURGERY PLUS CONCURRENT CHEMORADIATION IN NEWLY DIAGNOSED GBM PATIENTS. (11th November 2019) - Bota, Daniela; Taylor, Thomas; Picconi, David; Duma, Christopher; Aiken, Robert; LaRocca, Renato; Xiao-Tang, Kong; Fu, Beverly; Alsharif, Mohamad; Hsieh, Candace; Nistor, Gabriel; Dillman, Robert
Abstract: Newly-diagnosed glioblastoma (GBM) patients have a limited survival (18–24 months). In the last decade immunotherapy has improved survival for patients with other malignancies, but not GBM. Herein we present the design and initial enrollment results for the AV-GBM-1 single-arm phase 2 trial. The study enrolls patients with primary GBM who have undergone craniotomy, have a tumor cell culture established, and complete satisfactory leukapheresis prior to planned concurrent chemotherapy and radiation. Patients are scheduled to receive up to 8 vaccine injections at weeks 1, 2, 3, 8, 12, 16, 20 and 24. Blood samples are collected just prior to each injection. The primary endpoint is overall survival from date of enrollment for intent-to-treat with AV-GBM-1. The study has fully enrolled 26 of planned 55 patients. The cell line success rate is 30/32, with 6 in progress; successful completion of leukapheresis is 28/29. Two patients have completed all 8 doses, two discontinued after dose 3 and dose 6 because of progressive disease; 15 are currently in treatment, and 6 are about to start treatment. There have been seven SAE, all for hospitalizations related to GBM. For the first 8 treated patients, plasma samples from baseline and weeks 2, 3, and 8 have been analyzed for immune markers by RayBiotech Life Inc. using quantitative multiplex ELISA array. Markers reflecting Th1, Th2, Th17 pathways and B-cells, natural killer cells and cytotoxic T-lymphocytes increased in 7/8 patients. Principal component analysis demonstrates correlative marker groupings with early dominance of Th1/Th17 (weeks 1 and 2) followed by Th2/immunoglobulins at week 8. These findings show that these patient-specific dendritic cell vaccines are inducing pro-inflammatory responses similar to what was observed in a previous trial in melanoma. The study is progressing efficiently. Full enrollment data may be available for presentation at the time of the annual meeting.